Pensamento e discurso: A linguagem como mediação entre dialética e hermenêutica na filosofia de F.D. Schleiermacher - Silva, Francisco José da (2020)
One of the most relevant debates in philosophy in its contemporaneity is that concerning Dialectics and its relationship with Hermeneutics. These procedures are understood both in their methodological aspects, as forms of philosophizing, and in the discussion of their systematic and structural places. Dialectics, since the Greeks, has been conceived at first as a theory of the oppositions of the real (ontological view), as well as a way of conducting opposing theses presented in a debate, whereas in the philosophy of modernity it assumes an epistemological character. from a subjective conception of the antinomies of reason with Kant. Hermeneutics, in turn, stood out as an auxiliary procedure for understanding and interpreting specific texts (philological, juridical and sacred), such as ars interpetandi, until the beginning of modernity, but later assuming a theoretical status of understanding philosophy as such as in Heidegger and Gadamer. In this case, we justify the subject of our research and its fundamental hypothesis, which intends to address the thought of the philosopher Friedrich Daniel Schleiermacher (1768-1834), in his Dialectic foundation, as theory of knowledge and art of conducting a debate (in dialegesthai) in an essentially platonic perspective, thought of as a propaedeutic discipline and dependent on Hermeneutics, as well as in its aspect of universal application with regard to the question of language, its comprehension and interpretation. We emphasize that, in response to German Idealism, the Schleiermacherian approach presents itself as an alternative inspired by the rescue of the Dialectic that underlies Plato's thinking. In this sense, one of the main aspects considered by Schleiermacher is the place that will be occupied by language as a fundamental medium that allows us to think about the possibility of a convergence between Dialectic and Hermeneutics in its philosophical reflection. This convergence and dependence between these parts of his philosophy aims, first and foremost, to guarantee the grounding aspect of the systematic knowledge operated by the former, without falling into the risk of a claim to an absolute knowledge, supported by the understanding of this incarnate knowledge in the historicity and plurality of society. human language, object of the latter. In this sense, the question that arises in our research is, to analyze the conception of Dialectic developed in its relation with the Hermeneutics in Schleiermacher as a procedure capable of articulating his philosophy.